(untitled) (Research, Society and Development, 2023)
In the last decade there has been an expansion in the number of people who use online social networks as well as in the number of people who abuse psychoactive drugs. Given this, the article aims to identify the difficulties encountered by users of psychoactive drugs to start the treatment of addiction and to evaluate the use of online social networks as a tool to attract users. The theme of the study reveals the importance of the internet and social networks when the objective is to reach the patient in his natural environment and to promote tools capable of motivating him to actions capable of improving his life and well-being.